Nicaragua : Poverty Reduction Strategy Paper Second Progress Report. (IMF Staff Country Reports; Country Report ;, 2004)
The government of Nicaragua has worked toward adopting the necessary economic measures to put the country's economy on the course of fiscal sustainability and those that guarantee transparent and austere management, not affecting the most vulnerable population. The government has managed to protect social spending, providing resources for strategic sectors, improving performance indicators for health and education, and implementing reforms that will have a greater impact on these sectors. It is expected that the tendency for social spending will be maintained in the coming years.